Consensus statement for stability assessment and reporting for perovskite photovoltaics based on ISOS procedures - Khenkin, Mark V.; Katz, Eugene A.; Abate, Antonio; Bardizza, Giorgio; Berry, Joseph J.; Brabec, Christoph; Brunetti, Francesca; Bulovic, Vladimir; Burlingame, Quinn; Di Carlo, Aldo; Cheacharoen, Rongrong; Cheng, Yi-Bing; et al. (Nature Energy, 2020)
Improving the long-term stability of perovskite solar cells is critical to the deployment of this technology. Despite the great emphasis laid on stability-related investigations, publications lack consistency in experimental procedures and parameters reported. It is therefore challenging to reproduce and compare results and thereby develop a deep understanding of degradation mechanisms. Here, we report a consensus between researchers in the field on procedures for testing perovskite solar cell stability, which are based on the International Summit on Organic Photovoltaic Stability (ISOS) protocols. We propose additional procedures to account for properties specific to PSCs such as ion redistribution under electric fields, reversible degradation and to distinguish ambient-induced degradation from other stress factors. These protocols are not intended as a replacement of the existing qualification standards, but rather they aim to unify the stability assessment and to understand failure modes. Finally, we identify key procedural information which we suggest reporting in publications to improve reproducibility and enable large data set analysis.
CRIS-Team Scopus Importer:2020-02-04